Diphallia with Associated Anomalies: A Case Report and Literature Review - Pande Made Wisnu Tirtayasa; Robertus Bebet Prasetyo; Arry Rodjani (Case Reports in Urology)
Diphallia or penile duplication is an extremely rare congenital anomaly. It occurs once in every 5.5 million live births. The extent of penile duplication and the number of associated anomalies vary greatly, ranging from a double glans from a penis with no associated anomaly up to complete penile duplication associated with multiple anomalies. Here, we report a 12-year-old boy with complete bifid diphallia associated with bifid scrotum, epispadia, and pubic symphysis diastasis along with a review of the articles pertaining to this anomaly.